A teoria sartreana da consciência e o problema da imagem - Cunha, Kátia da Silva (2011)
This dissertation aims to presents the problem of construction of the image as it appears to consciousness in the work The Imaginary Phenomenological psychology of imagination (1940). In such work, Sartre (1905-1980) presents the imagination as a constitutive structure of essence of consciousness. In this sense, we investigate how images appear to consciousness and the role of the imaginary for the production of knowledge, which allows us to better understand in which sense the matter of Nothingness and unreality are important to understand several works of the author. We seek to demonstrate to which extent this study presents itself as an ontological problem. To do so, we present the various types of mental images and their respective supporting materials (analogon), as well as the types of relations we establish with the images. Through this study, it was also possible to conclude how much our ability to imagine relates to the issue of freedom, otherwise if we were not able to imagine, we would be absorbed by the intuitions of the real and we could not build a different world from the one we live in.